Extracellular vesicles in cardiac repair and regeneration: Beyond stem-cell-based approaches - Femminò, Saveria; Bonelli, Filippo; Brizzi, Maria Felice (Frontiers in Cell and Developmental Biology, 2022)
The adult human heart poorly regenerate after injury due to the low self-renewal capability retained by adult cardiomyocytes. In the last two decades, several clinical studies have reported the ability of stem cells to induce cardiac regeneration. However, low cell integration and survival into the tissue has limited stem-cell-based clinical approaches. More recently, the release of paracrine mediators including extracellular vesicles (EV) has been recognized as the most relevant mechanism driving benefits upon cell-based therapy. In particular, EV have emerged as key mediators of cardiac repair after damage, in terms of reduction of apoptosis, resolution of inflammation and new blood vessel formation. Herein, mechanisms involved in cardiac damage and regeneration, and current applications of EV and their small non-coding RNAs (miRNAs) in regenerative medicine are discussed.